2005
DOI: 10.1159/000089999
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of ST6Gal I Activity in Malignant and Transitional Tissue in Human Colorectal Cancer

Abstract: Objectives: The aim of the present study was to investigate the activity of CMP-NeuAc:Galβ(1,4)GlcNAc sialyltransferase (ST6Gal I) in colorectal cancer (CRC). Methods: ST6Gal I activity was determined in healthy, transitional and tumor tissues from the same patient using asialotransferrin and N-acetyllactosamine as acceptors. Results: ST6Gal I activities with asialotransferrin (n = 85) and N-acetyllactosamine (n = 40) as acceptors were statistically significantly enhanced in CRC tissue compared with healthy mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Mostafapour & Goldstein [26] reported that tumour cells with high metastatic potential tend to file a high ST6Gal I activity. Previous studies from our group [23] detected differences between enzyme activity of healthy tissue and transitional ones, in a reduced population of patients. If this difference is confirmed in subsequent analyses, it might seem that tissue cells suffer transitional changes of enzyme activity, perhaps as a prior episode for tumour processing.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Mostafapour & Goldstein [26] reported that tumour cells with high metastatic potential tend to file a high ST6Gal I activity. Previous studies from our group [23] detected differences between enzyme activity of healthy tissue and transitional ones, in a reduced population of patients. If this difference is confirmed in subsequent analyses, it might seem that tissue cells suffer transitional changes of enzyme activity, perhaps as a prior episode for tumour processing.…”
Section: Discussionmentioning
confidence: 83%
“…[23]. The reaction mixture, in a total volume of 100 μL, contained: NaF 4 mM, MnCl 2 5 mM, Triton X-100 0.2% (v/v), MES buffer 40 mM (pH 6), 50 μg enzyme solution, 0.9 mg AST and 200 μM CMP-NeuAc [1 μM CMP- 14 C-NeuAc (specific activity 9.2-12 GBq/mmol, 77.4-80.32 μM, Amersham Biosciences, Uppsala, Sweden) and 199 μM CMP-NeuAc (Sigma, St. Louis, MO, USA)] as donor substrate.…”
Section: Methodsmentioning
confidence: 99%
“…In colon cancer ST6Gal I and ST3Gal III increased their expression in carcinoma specimens [15]. ST3Gal III was prominently increased in cancer tissues compared with non-malignant colorectal mucosa [16] and an elevation of ST6Gal I activity was observed in malignant and transitional tissue [17]. In gastric cancer, high levels of ST3Gal III a in the tumour tissue correlated with secondary tumour recurrence [18].…”
Section: Introductionmentioning
confidence: 98%
“…ST6Gal I activity is also associated with the acquisition of the neoplastic phenotype (15), as well as the resistance to irinotecan (16) and Fas-mediated apoptosis (17). Furthermore, in CRC patients, ST6Gal I activity is greater in tumor than in healthy tissue (18,19), particularly in metastatic tumors (20). The CDw75 antigen is expressed in the majority of colorectal tumors, where its expression is augmented with regard to the healthy mucosa (21,22).…”
Section: Introductionmentioning
confidence: 99%